2021
DOI: 10.1186/s43045-021-00087-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of suicidal ideations among patients with obsessive-compulsive disorder in Egypt

Abstract: Background Suicidal ideations were reported in many studies among patient with obsessive-compulsive disorder (OCD); this study aimed to evaluate the prevalence and factors associated with current suicidal ideations among Egyptian patients with obsessive-compulsive disorder (OCD). A consecutive sample of 120 Egyptian OCD patients was included in the study. OCD was diagnosed using the structured clinical interview for DSM-V axis Ι disorders, clinical version (SCID-I-CV). Yale-Brown Obsessive Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…While, Sehlo et al,(2021), found no significant relationship between age and suicidal thoughts or obsessive-compulsive disorder at P value (0.8).…”
Section: Discussionmentioning
confidence: 80%
“…While, Sehlo et al,(2021), found no significant relationship between age and suicidal thoughts or obsessive-compulsive disorder at P value (0.8).…”
Section: Discussionmentioning
confidence: 80%
“…For instance, a study conducted among Egyptian Muslim patients with OCD found religious obsessions to be the highest predictor of SI in this population. 40 Therefore, it is important to consider an individual’s cultural and experiential context when approaching assessments and treatment. Severity of overall OCD symptoms and related disability does consistently associate with a higher likelihood of experiencing SI, as well as longer duration of illness prior to treatment and earlier age of onset.…”
Section: Methodsmentioning
confidence: 99%
“…Particular symptoms, such as symmetry and order obsessions and compulsions, repeating and trust seeking compulsions, unacceptable or taboo thoughts and obsessions, contamination obsessions, cleaning and washing compulsions, and sexual or religious obsessions, have been more frequently associated with SI and SA. 5,6,17,25,[27][28][29][30][31]39,40 Unacceptable thoughts demonstrate the strongest correlation with suicidality, likely due to a higher level of distress accompanying an already distressing experience which is then accentuated by violating expectations dictated by social norms. This remains consistent after controlling for other symptom dimensions, comorbidities, and overall symptom severity.…”
Section: Ocd Phenotypesmentioning
confidence: 99%
“…En ese sentido, la ideación, planificación, autolesión e intento son los principales precedentes de muerte por suicidio (Sarfo et al, 2023;Sehlo et al, 2021;Wu et al, 2021). La relevancia del riesgo suicida se basa en la magnitud de la gravedad del caso: gravedad baja, se vincula con presentar pensamientos suicidas, y alta gravedad, involucra ideación, plan e intento de suicidio (Wang et al, 2014).…”
Section: Introductionunclassified